2022
DOI: 10.21873/invivo.13041
|View full text |Cite
|
Sign up to set email alerts
|

The Barthel Index for Predicting Postoperative Complications in Elderly Patients Undergoing Abdominal Surgery: A Prospective Single-center Study

Abstract: Background/Aim: The Barthel index and Katz index are useful in assessing the physical function status of patients. We prospectively evaluated the relationship between the Barthel and Katz indices and postoperative complications in older patients undergoing gastrointestinal surgery. Patients and Methods: We enrolled 250 patients aged ≥65 years who underwent gastrointestinal surgery between September 2018 and April 2020. Postoperative complications within 30 days after surgery were categorized using the Clavien-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While the original index quantifies mortality risk by scoring comorbidities based on their potential to impact mortality, the age-adjusted CCI incorporates age into the scoring system, offering a more comprehensive risk assessment by accounting for both comorbidity severity and the patient’s age [ 17 ]. Additionally, the Barthel index for Activities of Daily Living (ADL) at the time of injury was collected from patient charts to gain insights into the patient’s functional status pre-injury [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…While the original index quantifies mortality risk by scoring comorbidities based on their potential to impact mortality, the age-adjusted CCI incorporates age into the scoring system, offering a more comprehensive risk assessment by accounting for both comorbidity severity and the patient’s age [ 17 ]. Additionally, the Barthel index for Activities of Daily Living (ADL) at the time of injury was collected from patient charts to gain insights into the patient’s functional status pre-injury [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Demographic variables, information regarding the consumption of toxins, such as tobacco and the existence of comorbidities, such as ischemic heart disease, respiratory disease, diabetes mellitus, immunosuppressive therapy (corticosteroids, infliximab, and methotrexate), kidney failure, obesity and hypothyroidism, and follow‐up data were obtained from the medical records. Frailty assessment was carried out on all patients using Barthel index 15 …”
Section: Methodsmentioning
confidence: 99%
“…Frailty assessment was carried out on all patients using Barthel index. 15 Radiological parameters, such as anatomical location, modified Neff severity classification, 14 length of colonic involvement, and location of perforations and/or abscesses (antimesenteric or free, mesenteric, and parietal peritoneum), were analyzed on abdominal CT images with intravenous contrast and reviewed by expert radiologists.…”
Section: Variables Studiedmentioning
confidence: 99%
“…Another challenge lies in the management of perioperative pain in elderly patients. Not only the number of procedures performed on patients over 65 years of age increases significantly, but also older patients are at increased risk of adverse postoperative outcomes ( 15 , 16 ). In prospective cohort study conducted in the United States, patients aged 80 and above showed significantly higher 30-day all-cause mortality than younger patients ( 17 ).…”
Section: Introductionmentioning
confidence: 99%